Motion Design in Digital Media: Its Impact on the Development of Visual Messages and User Interaction - Mansour, Qusai Saleh Othman (Journal of Ecohumanism, 2025)
This research addresses "Motion Design in Digital Media: Its Impact on the Development of Visual Messages and User Interaction," focusing on the impact of animated graphics in the development of media messages and audience engagement. With the rapid growth of digital technology, motion design has become one of the essential tools contributing to enhancing the user experience and increasing the effectiveness of media messages. The study aims to explore how motion design can enhance interaction with digital content, including advertisements, e-learning, and other digital media. It also emphasizes the effects of motion, timing, and visual coordination in attracting attention and strengthening the power of messages to influence and persuade. The research concluded several key findings, including: motion design enhances audience attention, improves user experience through interaction with moving elements, and aids in simplifying complex messages. It was also found that excessive use of motion could lead to distraction, negatively affecting the effectiveness of the message. On the other hand, motion design requires attention to quality and compatibility with various devices to ensure a smooth user experience. The study recommends improving techniques used in motion design, avoiding excessive motion, and focusing on user-content interaction to enhance the visual and media experience